The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0890334420939549
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative to Mother’s Own Milk: Maternal Awareness of Donor Human Milk and Milk Banks

Abstract: Background The use of donor human milk is rising. Maternal awareness of donor human milk use, milk donation, and milk banks has not been well described in the United States. Research Aims To explore maternal experience, knowledge, and attitudes regarding donor human milk use and milk donation. We also assessed counseling by medical providers about donor human milk use and donation. Methods A cross-sectional prospective survey design was used in this study. We anonymously surveyed mothers ( N = 73) attending th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…More than two-thirds of the women included in this study reported that they had never heard of HMB before. Similar studies report that women have higher awareness in countries where HMBs are used [21][22][23] and levels of awareness about HMB are low in other countries [24][25][26]. Although the respondents' awareness level of HMB was low, at the end of the study, more than half of the respondents supported the founding of an HMB in Turkey.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…More than two-thirds of the women included in this study reported that they had never heard of HMB before. Similar studies report that women have higher awareness in countries where HMBs are used [21][22][23] and levels of awareness about HMB are low in other countries [24][25][26]. Although the respondents' awareness level of HMB was low, at the end of the study, more than half of the respondents supported the founding of an HMB in Turkey.…”
Section: Discussionsupporting
confidence: 54%
“…In this study, the majority of the women had heard about wet nursing and reported that they would be willing to be wet nurses; only one in eight, however, had experienced this. Although the use of wet nurses has decreased significantly today [7], mothers' willingness to be wet nurses is also supported by the literature [19,21].…”
Section: Discussionmentioning
confidence: 94%
“…A demographic data sheet was completed by the participants. The research team developed a semistructured interview guide (figure 1) based on their clinical expertise and a literature review 17 18 21. Before conducting participant interviews, team members revised the interview guide after pilot testing it with two postpartum mothers.…”
Section: Methodsmentioning
confidence: 99%
“…Previous publications have reported experiences of mothers with DHM in other countries, including mothers of premature infants 16–21. There is no published study on experiences of mothers with premature infants in a multiracial Asian society; therefore, we have embarked on this study in our institution.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the human milk bank (HMB) is the main alternative for promoting breastfeeding and performing HM collection, processing, and quality control activities. The administration of this diet is commonly done with the aid of an infusion pump (which keeps the diet flow controlled) or by gavage (which allows flow according to the force of gravity; Ellsworth et al, 2020).…”
Section: Introductionmentioning
confidence: 99%